Preparation method of copper-nickel-silicon-cobalt-magnesium alloy and copper-nickel-silicon-cobalt-magnesium alloy

By adding Co and Mg elements to Cu-Ni-Si alloys, the mechanical properties and conductivity of the alloys are optimized, and the problem that existing alloys are difficult to take into account both the conductivity and mechanical properties is solved, and a higher comprehensive performance is achieved.

CN119800148AActive Publication Date: 2025-04-11INSTITUTE OF MATERIALS & INTELLIGENT MANUFACTURING JIANGXI ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411930871.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

It is difficult for existing Cu-Ni-Si series alloys to take into account both high conductivity and good mechanical properties.

Method used

By adding Co and Mg elements to the Cu-Ni-Si alloy, the precipitation of the (Ni, Co)2Si phase is promoted, and the mechanical properties of the alloy are optimized while maintaining a high conductivity by controlling the content of Mg elements.

Benefits of technology

The high conductivity and good mechanical properties of the alloy are achieved, and the comprehensive performance of Cu-Ni-Si alloy is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800148A_ABST
    Figure CN119800148A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of alloy preparation, and discloses a preparation method of a copper-nickel-silicon-cobalt-magnesium alloy and the copper-nickel-silicon-cobalt-magnesium alloy, Co is added to promote precipitation of a (Ni, Co) 2Si phase in the copper alloy, Mg is added to promote complete precipitation of a precipitated phase in the copper alloy, and the copper-nickel-silicon-cobalt-magnesium alloy is obtained. Therefore, in order to further improve the performance of the Cu-Ni-Si alloy for the high-end integrated circuit lead frame, Co and Mg elements are added on the basis of Cu-Ni-Si ternary components, sufficient precipitation of a (Ni, Co) 2Si phase is promoted by changing the content of the Mg element, meanwhile, by controlling the content of the Mg element, it is ensured that the alloy has certain electric conductivity, and meanwhile, the Cu-Ni-Si alloy for the high-end integrated circuit lead frame is prepared. And it can be ensured that the whole alloy has certain mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of alloy preparation, and in particular to a copper-nickel-silicon-cobalt-magnesium alloy preparation method and a copper-nickel-silicon-cobalt-magnesium alloy. Background Art

[0002] Cu-Ni-Si series alloys have comprehensive properties such as high strength, moderate electrical and thermal conductivity, and good resistance to high temperature softening.

[0003] In the prior art, in order to improve the strength of the alloy, Cu-Ni-Si series alloys are usually strengthened by precipitation, and the process involved is generally a solution treatment-rolling-aging process. Ni, Si and other alloys are dissolved in the copper matrix through solution treatment, and a large number of fine and uniform Ni2Si phase particles are precipitated during the subsequent rolling and aging treatment, which has the effect of precipitation strengthening. The Si content in the copper matrix is ​​very harmful to the conductivity of the copper alloy. With the precipitation of Ni2Si, the conductivity of the alloy is gradually improved.

[0004] However, the Cu-Ni-Si series alloys still have the defects of relatively poor mechanical properties and electrical conductivity. Summary of the invention

[0005] In view of this, the present invention provides a method for preparing a copper-nickel-silicon-cobalt-magnesium alloy and a copper-nickel-silicon-cobalt-magnesium alloy to solve the problem in the prior art that both electrical conductivity and mechanical properties cannot be taken into account at the same time.

[0006] In a first aspect, the present invention provides a nickel-silicon-cobalt-magnesium alloy, wherein, according to the mass fraction of the alloy components, Ni is 1.80%, Si is 0.62%, Co is 1.1%, Mg is 0.12%-0.24%, and the balance is copper.

[0007] Beneficial effects: Adding Co element can promote the precipitation of (Ni, Co)2Si phase in copper alloy, and adding Mg element can promote the complete precipitation of precipitation phase in copper alloy. Therefore, in order to further improve the performance of Cu-Ni-Si alloy for high-end integrated circuit lead frame, this study added Co and Mg elements on the basis of Cu-Ni-Si ternary components, and promoted the full precipitation of (Ni, Co)2Si phase by changing the Mg content. At the same time, by controlling the Mg content, while ensuring that the alloy has a certain conductivity, it can ensure that the alloy as a whole has certain mechanical properties.

[0008] In an optional embodiment,

[0009] On the other hand, the present invention provides a method for preparing a copper-nickel-silicon-cobalt-magnesium alloy, which is used to prepare the nickel-silicon-cobalt-magnesium alloy provided by the present invention, and comprises the following steps: placing a high-purity copper raw material, a nickel raw material, a silicon raw material and a cobalt raw material into a smelting device for melting; evacuating the smelting device to reduce the air pressure inside the smelting device to below 20Pa; introducing an inert gas into the smelting device to increase the air pressure inside the smelting device to between 0.04 and 0.05Mpa; introducing a magnesium raw material into the smelting device, and starting the smelting device to melt the magnesium raw material; allowing the metal melt obtained after smelting to stand, and taking out the alloy ingot after cooling to room temperature; and smelting the obtained alloy ingot. A solution treatment process is performed, wherein the solution treatment temperature is 800°C-900°C and the solution treatment time is 5 hours; a rolling process is performed on the alloy ingot after the solution treatment process, including: a rough rolling process, wherein the rolling temperature is room temperature, the single pass is 20%, the roller speed is 30 rpm, and the rough rolling reduction is 90%; a finishing rolling process, wherein the rolling temperature is room temperature, the single pass is 10%, the roller speed is 20 rpm, and the finishing rolling reduction is 90%; and the total rolling reduction is 99%; after the rolling process, the process also includes: performing an aging treatment on the rolled alloy at 300-400°C for 10-40 minutes, and air cooling to room temperature after aging.

[0010] Furthermore, the vacuum induction melting furnace is provided with a copper tube, and the magnesium raw material is introduced into the vacuum induction melting furnace through the copper tube.

[0011] Furthermore, before the rolling operation step, the alloy ingot is cleaned, including: grinding with sandpaper and cleaning with acetone and alcohol.

[0012] Another aspect of the present invention provides a method for preparing a copper-nickel-silicon-cobalt-magnesium alloy, which is used to prepare the nickel-silicon-cobalt-magnesium alloy provided by the present invention, comprising the following steps:

[0013] Putting high-purity copper raw materials, nickel raw materials, silicon raw materials and cobalt raw materials into a smelting device for melting; performing a vacuum operation on the smelting device to reduce the air pressure inside the smelting device to below 20Pa; introducing an inert gas into the smelting device to increase the air pressure inside the smelting device to between 0.04 and 0.05Mpa; introducing a magnesium raw material into the smelting device, and starting the smelting device to melt the magnesium raw material; placing the metal melt obtained after smelting, and taking out the alloy ingot after cooling to room temperature; performing a solid solution operation on the obtained alloy ingot, wherein the solid solution temperature is 800°C-900°C, and the solid solution time is 5 hours; The alloy ingot after the solution treatment is subjected to a rolling operation, including: keeping the alloy sample at 760°C-800°C for 0.5h; hot rolling on a two-roll mill, the rolling conditions are: 30% for a single pass, 30 roll speed per minute, and a hot rolling reduction of 50-55%; after the alloy sample is air-cooled to room temperature, rough rolling is performed on a two-roll mill, the rolling conditions are: room temperature, 20% for a single pass, 30 roll speed per minute, and a rough rolling reduction of 80-85%; the rolled alloy is subjected to an aging treatment at 430°C for 0.5h-4h, and air-cooled to room temperature after aging.

[0014] Furthermore, the vacuum induction melting furnace is provided with a copper tube, and the magnesium raw material is introduced into the vacuum induction melting furnace through the copper tube.

[0015] Furthermore, before the rolling operation step, the alloy ingot is cleaned, including: grinding with sandpaper and cleaning with acetone and alcohol. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 It is a partial process flow chart of one of the preparation methods provided by the present invention;

[0018] Figure 2 This is a phase diagram of the nickel-silicon-cobalt-magnesium alloy provided by the present invention;

[0019] Figure 3 is the conductivity corresponding to the first group of samples provided by the present invention;

[0020] Figure 4 is the tensile strength corresponding to the first group of samples provided by the present invention;

[0021] Figure 5 is the conductivity corresponding to the second group of samples provided by the present invention;

[0022] Figure 6 is the tensile strength corresponding to the second group of samples provided by the present invention;

[0023] Figure 7 is the conductivity corresponding to the third group of samples provided by the present invention;

[0024] Figure 8 is the tensile strength corresponding to the third group of samples provided by the present invention;

[0025] Fig. 9 is the conductivity corresponding to the fourth group of samples provided by the present invention;

[0026] Fig.10 is the tensile strength corresponding to the fourth group of samples provided by the present invention;

[0027] Fig.11 is the conductivity corresponding to the fifth group of samples provided by the present invention;

[0028] Fig.12 is the tensile strength corresponding to the fifth group of samples provided by the present invention;

[0029] Fig.13 is the conductivity corresponding to the sixth group of samples provided by the present invention;

[0030] Fig.14 is the tensile strength corresponding to the sixth group of samples provided by the present invention;

[0031] Fig.15 is the conductivity corresponding to the seventh group of samples provided by the present invention;

[0032] Fig.16 is the tensile strength corresponding to the seventh group of samples provided by the present invention;

[0033] Fig.17 It is a schematic diagram of the strength test of the sample in the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0035] In order to solve the problems existing in the above-mentioned related technologies, according to a first aspect of the present invention, a method for preparing a copper-nickel-silicon-cobalt-magnesium alloy is provided, comprising the following steps: placing a high-purity copper raw material, a nickel raw material, a silicon raw material and a cobalt raw material into a smelting device for melting; evacuating the smelting device to reduce the air pressure inside the smelting device to below 20Pa; introducing an inert gas into the smelting device to increase the air pressure inside the smelting device to between 0.04 and 0.05Mpa; introducing a magnesium raw material into the smelting device, and starting the smelting device to melt the magnesium raw material; and allowing the molten metal obtained after smelting to stand, and taking out the alloy ingot after cooling to room temperature.

[0036] In this embodiment, combined with Figure 1-Figure 17 The reaction mechanism involved is as follows:

[0037] Adding Co element can promote the precipitation of (Ni, Co)2Si phase in copper alloy, and adding Mg element can promote the complete precipitation of precipitation phase in copper alloy, so in order to further improve the performance of Cu-Ni-Si alloy for high-end integrated circuit lead frame; In this embodiment, it can be seen from the accompanying drawings that after adding magnesium element, the electrical conductivity of the alloy has hardly changed, but its tensile strength has increased significantly. That is, by introducing magnesium element, firstly, the complete precipitation of precipitation phase in copper alloy can be promoted, and in addition, the electrical conductivity can be controlled while the mechanical properties of alloy finishing can be additionally improved, so that the alloy has a relatively good comprehensive performance.

[0038] On the basis of Cu-Ni-Si ternary components, Co and Mg elements were added, and by changing the Mg content, such as Figure 2 As shown, the precipitation of (Ni, Co)2Si phase is promoted and the Si content in the matrix is ​​reduced to obtain a Cu-Ni-Si-Co-Mg alloy with good mechanical properties and electrical conductivity. At the same time, a preparation method of a high-strength and high-conductivity copper-nickel-silicon-cobalt-magnesium alloy is provided, which has a short process flow, simple preparation technology and low cost.

[0039] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.

[0040] Example 1

[0041] The present embodiment provides a nickel-silicon-cobalt-magnesium alloy, wherein, according to the mass fraction of the alloy components, Ni is 1.80%, Si is 0.62%, Co is 1.1%, Mg is 0.12%-0.24%, and the balance is copper.

[0042] Embodiment 2:

[0043] This embodiment provides a method for preparing a nickel-silicon-cobalt-magnesium alloy, comprising the following steps:

[0044] Putting high-purity copper raw materials, nickel raw materials, silicon raw materials and cobalt raw materials into a smelting device for melting;

[0045] Specifically, raw materials are prepared according to the alloy component mass fractions of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%.

[0046] Evacuate the smelting equipment to reduce the pressure inside the smelting equipment to below 20Pa;

[0047] In this embodiment, the smelting equipment is not limited, as long as the alloy can be melted. As an implementation method, a vacuum induction melting furnace is used in this embodiment for smelting. Specifically, the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles are added to the graphite crucible in the vacuum induction melting furnace. In this embodiment, in order to achieve the addition of magnesium elements, a copper tube is provided on the vacuum induction melting furnace, and the magnesium raw material is passed into the vacuum induction melting furnace through the copper tube.

[0048] Furthermore, an inert gas is introduced into the smelting equipment to increase the gas pressure inside the smelting equipment to between 0.04-0.05Mpa;

[0049] Through the above-mentioned operation steps, an inert gas environment can be formed inside the smelting equipment, thereby preventing the magnesium element to be introduced subsequently from being oxidized.

[0050] Furthermore, magnesium raw materials are introduced into the smelting equipment, and the smelting equipment is started to melt the magnesium raw materials; the metal melt obtained after smelting is allowed to stand, and the alloy ingot is taken out after cooling to room temperature.

[0051] Specifically, a secondary feeding copper tube is provided on the vacuum induction melting furnace. First, high-purity magnesium particles are sealed in the secondary feeding copper tube, the melting furnace is closed and the air is evacuated to 13Pa, at which time a vacuum environment is formed, and then argon gas is introduced to a pressure of 0.04-0.05Mpa to form an inert gas environment. The metal particles in the crucible are completely melted by induction heating, and then left to stand for 2-3 minutes. High-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and then left to stand for 3-5 minutes. Finally, the alloy melt is poured into a mold, and the ingot is taken out after cooling to room temperature.

[0052] Adding the Co element can promote the precipitation of (Ni, Co)2Si phase in the copper alloy, and adding the Mg element can promote the complete precipitation of the precipitation phase in the copper alloy. Therefore, in order to further improve the performance of the Cu-Ni-Si alloy for high-end integrated circuit lead frames; in this embodiment, after adding the magnesium element, the electrical conductivity of the alloy has hardly changed, but its tensile strength has increased significantly. That is, by introducing the magnesium element, firstly, the complete precipitation of the precipitation phase in the copper alloy can be promoted, and in addition, the electrical conductivity can be controlled while the mechanical properties of the alloy finishing can be additionally improved, thereby controlling the alloy to have a relatively good comprehensive performance.

[0053] Furthermore, the copper-nickel-silicon-cobalt-magnesium alloy preparation method provided in this embodiment also includes: performing a solid solution operation on the obtained alloy ingot, wherein the solid solution temperature is 800°C-900°C and the solid solution time is 5 hours.

[0054] Specifically, the alloy ingot was cut into blocks by wire cutting, followed by solution treatment, kept at 850°C for 5 hours and then water-cooled to room temperature, polished with sandpaper, and then cleaned with acetone and alcohol for surface impurities.

[0055] Furthermore, the copper-nickel-silicon-cobalt-magnesium alloy preparation method provided in this embodiment further includes: rolling operation on the alloy ingot after solid solution operation treatment, including: rough rolling step: rolling temperature is room temperature, single pass is 20%, roll speed is 30 rpm, and rough rolling reduction is 90%; finishing rolling step: rolling temperature is room temperature, single pass is 10%, roll speed is 20 rpm, finishing rolling reduction is 90%; total rolling reduction is 99%.

[0056] In this embodiment, before the rolling operation step, a cleaning operation of the alloy ingot is also included, including: grinding with sandpaper and cleaning with acetone and alcohol.

[0057] Furthermore, the copper-nickel-silicon-cobalt-magnesium alloy preparation method provided in this embodiment, after the rolling operation step, also includes: aging the rolled alloy at 300° C. for 20 minutes, and air-cooling to room temperature after aging.

[0058] Strip samples are obtained by wire cutting, and their microstructure, conductivity and mechanical properties are analyzed and tested.

[0059] Embodiment 3:

[0060] This embodiment is made on the basis of embodiment 2, and the main difference is: the content of magnesium element is different.

[0061] Prepare raw materials according to the alloy component mass fraction of Ni 1.80%, Si 0.62%, Co 1.1%, Mg 0.24%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%. Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles into the secondary feeding copper tube, close the melting furnace and extract the air to 13Pa, and then introduce argon gas to the pressure of 0.04-0.05Mpa. Completely melt the metal particles in the crucible by induction heating, let it stand for 2-3 minutes, add the high-purity magnesium particles into the molten metal through the secondary feeding copper tube, let it stand for 3-5 minutes, and finally pour the alloy melt into the mold, cool it to room temperature and take out the ingot. The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was cooled to room temperature by water. After being polished with sandpaper, the surface impurities were cleaned with acetone and alcohol. The alloy sample was rough rolled on a two-roll mill. The rolling conditions were room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction was 90%. Then the sample was finished rolled on a four-roll mill. The rolling conditions were room temperature, single pass 10%, roll speed 20 rpm, and finishing rolling reduction was 90%. The total rolling reduction was 99%. The cold-rolled alloy sample was aged at 300℃ for 40min, and then air-cooled to room temperature. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.

[0062] Comparative Example 1:

[0063] Prepare raw materials according to the alloy component mass fraction of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%.

[0064] Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles into the secondary feeding copper tube, close the melting furnace and evacuate the air to 13Pa, then introduce argon gas to the pressure of 0.04-0.05Mpa. The metal particles in the crucible are completely melted by induction heating, and then allowed to stand for 2-3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and then allowed to stand for 3-5 minutes. Finally, the alloy melt is poured into the mold, and the ingot is taken out after cooling to room temperature. The alloy ingot is cut into blocks by wire cutting, and then solution treatment is carried out. After being kept at 850℃ for 5 hours, it is cooled to room temperature with water, and the surface impurities are cleaned with acetone and alcohol after being polished with sandpaper. The alloy samples were rough rolled on a two-roll mill, rolling conditions: room temperature, single pass 20%, roll speed 30 rpm, rough rolling reduction 90%; then the samples were finish rolled on a four-roll mill, rolling conditions: room temperature, single pass 10%, roll speed 20 rpm, finish rolling reduction 90%; total rolling reduction 99%. Cold-rolled alloy samples were aged at 300°C for 10 minutes, and then air-cooled to room temperature. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.

[0065] The samples obtained in Example 1, Example 2 and Comparative Example 1 were set as the first group of samples and tested. The test results are as follows:

[0066] Table 1 Mechanical properties test results of the first group of samples

[0067] Time limit 0% Mg 0.12% Mg 0.24% Mg min MPa MPa MPa 0 505 648 692.2 10 536.1 683.3 695.5 20 488.8 685.1 663 30 506.1 675.01 669.6 40 493.9 664.2 574.1

[0068] Table 2 Increment of mechanical properties of the first group of specimens

[0069] Time limit 0% Mg 0.12% Mg 0.24% Mg min 0 0 28.32% 37.07% 10 0 27.46% 29.73% 20 0 40.16% 35.64% 30 0 33.37% 32.31% 40 0 34.48% 16.24% average value 32.76% 30.2%

[0070] Table 3 Test results of conductivity of the first group of samples

[0071] Time limit 0% Mg 0.12% Mg 0.24% Mg min %IACS %IACS %IACS 0 39.90782 38.15191 36.46133 10 43.37981 40.79989 38.91011 20 43.37359 42.17397 39.52091 30 42.02735 41.27406 39.42829 40 44.026 41.77813 37.74119

[0072] Table 4 Increment of conductivity of the first group of samples

[0073] Time limit 0% Mg 0.12% Mg 0.24% Mg min 0 0 -4.40% -8.64% 10 0 -5.95% -10.30% 20 0 -2.77% -8.88% 30 0 -1.79% -6.18% 40 0 -5.11% -14.28% average value -4% -9.66%

[0074] Combining the contents in Tables 1 to 4, it can be seen that in the first group of samples, when the content of magnesium element increases to 0.12%, its mechanical properties increase by 32.76%, but its electrical conductivity only changes by 4%.

[0075] In the first group of samples, when the magnesium content increased to 0.24%, its mechanical properties increased by 30.2%, but its electrical conductivity only changed by 9.66%.

[0076] Embodiment 4:

[0077] This embodiment is made on the basis of embodiment 2. Raw materials are prepared according to the alloy component mass fractions of Ni of 1.80%, Si of 0.62%, Co of 1.1%, Mg of 0.12%, and the balance of copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%. The prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles are added to the graphite crucible in the vacuum induction melting furnace, and the high-purity magnesium particles are sealed in the secondary feeding copper tube. The melting furnace is closed and the air is extracted to 13Pa, and then argon gas is introduced to the pressure of 0.04-0.05Mpa. The metal particles in the crucible are completely melted by induction heating, and the mixture is allowed to stand for 2-3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and the mixture is allowed to stand for 3-5 minutes. Finally, the alloy melt is poured into the mold, and the ingot is taken out after cooling to room temperature. The alloy ingot was cut into blocks by wire cutting, followed by solution treatment, kept at 850℃ for 5h, cooled to room temperature, polished with sandpaper, and cleaned with acetone and alcohol for surface impurities. The alloy sample was rough rolled on a two-roll mill, with rolling conditions: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 90%; then the sample was finish rolled on a four-roll mill, with rolling conditions: room temperature, single pass 10%, roll speed 20 rpm, and finish rolling reduction of 90%; the total rolling reduction was 99%.

[0078] The main difference lies in the aging temperature. The cold-rolled alloy samples were aged at 350°C for 20 minutes and then air-cooled to room temperature. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.

[0079] Embodiment 5:

[0080] This embodiment is made on the basis of embodiment 2, and the main differences are: different magnesium content and different aging treatment issues.

[0081] Prepare raw materials according to the alloy component mass fraction of Ni 1.80%, Si 0.62%, Co 1.1%, Mg 0.24%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%. Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles into the secondary feeding copper tube, close the melting furnace and extract the air to 13Pa, and then introduce argon gas to the pressure of 0.04-0.05Mpa. Completely melt the metal particles in the crucible by induction heating, let it stand for 2-3 minutes, add the high-purity magnesium particles into the molten metal through the secondary feeding copper tube, let it stand for 3-5 minutes, and finally pour the alloy melt into the mold, cool it to room temperature and take out the ingot. The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was cooled to room temperature by water. After being polished with sandpaper, the surface impurities were cleaned with acetone and alcohol. The alloy sample was rough rolled on a two-roll mill. The rolling conditions were room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction was 90%. Then the sample was fine rolled on a four-roll mill. The rolling conditions were room temperature, single pass 10%, roll speed 20 rpm, and finishing rolling reduction was 90%. The total rolling reduction was 99%. The cold-rolled alloy sample was aged at 350℃ for 40min, and then air-cooled to room temperature. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.

[0082] Comparative Example 2:

[0083] Comparative Example 2 is made on the basis of Comparative Example 1. Raw materials are prepared according to the alloy component mass fractions of Ni of 1.80%, Si of 0.62%, Co of 1.1%, Mg of 0%, and the balance of copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%. The prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles are added to the graphite crucible in the vacuum induction melting furnace, and the high-purity magnesium particles are sealed in the secondary feeding copper tube. The melting furnace is closed and the air is extracted to 13Pa, and then argon gas is introduced to the pressure of 0.04-0.05Mpa. The metal particles in the crucible are completely melted by induction heating, and the mixture is allowed to stand for 2-3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and the mixture is allowed to stand for 3-5 minutes. Finally, the alloy melt is poured into a mold, and the ingot is taken out after cooling to room temperature. The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was cooled to room temperature by water. After being polished with sandpaper, the surface impurities were cleaned with acetone and alcohol. The alloy sample was rough rolled on a two-roll mill. The rolling conditions were room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction was 90%. Then the sample was finished rolled on a four-roll mill. The rolling conditions were room temperature, single pass 10%, roll speed 20 rpm, and finishing rolling reduction was 90%. The total rolling reduction was 99%. The cold-rolled alloy sample was aged at 350℃ for 10min, and then air-cooled to room temperature. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.

[0084] The samples obtained in Example 4, Example 5 and Comparative Document 2 were set as the second sample group, and the test results obtained were as follows:

[0085] Table 5 Mechanical properties test results of the second group of samples

[0086]

[0087]

[0088] Table 6 Mechanical property increment of the second group of specimens

[0089] Time limit 0% Mg 0.12% Mg 0.24% Mg min MPa MPa MPa 0 0 28.32% 37.07% 10 0 40.36% 30.55% 20 0 48.06% 48.79% 30 0 33.93% 44.36% 40 0 48.88% 37.50% average value 39.91% 39.65%

[0090] Table 7 Test results of the second group of conductivity of samples

[0091] Time limit 0% Mg 0.12% Mg 0.24% Mg min %IACS %IACS %IACS 0 39.90782 38.15191 36.46133 10 45.65904 43.93641 41.68083 20 49.42942 44.51266 43.3511 30 50.11967 44.56421 43.44804 40 50.92238 45.07294 43.80021

[0092] Table 8 Conductivity increment of the second group of samples

[0093] Time limit 0% Mg 0.12% Mg 0.24% Mg min 0 0 -4.40% -8.64% 10 0 -3.77% -8.71% 20 0 -9.95% -12.30% 30 0 -11.08% -13.31% 40 0 -11.49% -13.99% average value -8.4% -11.39%

[0094] Combining the contents in Tables 5 to 8, it can be seen that in the second group of samples, when the content of magnesium element increases to 0.12%, its mechanical properties increase by 39.91%, but its electrical conductivity only changes by 8.4%.

[0095] In the second group of samples, when the magnesium content increased to 0.24%, its mechanical properties increased by 39.65%, but its electrical conductivity only changed by 11.39%.

[0096] Embodiment 6:

[0097] This embodiment is made on the basis of embodiment 2. Raw materials are prepared according to the alloy component mass fractions of Ni of 1.80%, Si of 0.62%, Co of 1.1%, Mg of 0.12%, and the balance of copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%. The prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles are added to the graphite crucible in the vacuum induction melting furnace, and the high-purity magnesium particles are sealed in the secondary feeding copper tube. The melting furnace is closed and the air is extracted to 13Pa, and then argon gas is introduced to the pressure of 0.04-0.05Mpa. The metal particles in the crucible are completely melted by induction heating, and the mixture is allowed to stand for 2-3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and the mixture is allowed to stand for 3-5 minutes. Finally, the alloy melt is poured into the mold, and the ingot is taken out after cooling to room temperature. The alloy ingot was cut into blocks by wire cutting, followed by solution treatment, kept at 850℃ for 5h, cooled to room temperature, polished with sandpaper, and cleaned with acetone and alcohol for surface impurities. The alloy sample was rough rolled on a two-roll mill, with rolling conditions: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 90%; then the sample was finish rolled on a four-roll mill, with rolling conditions: room temperature, single pass 10%, roll speed 20 rpm, and finish rolling reduction of 90%; the total rolling reduction was 99%.

[0098] The main difference lies in the aging temperature, where the cold-rolled alloy samples were aged at 400°C for 20 minutes and then air-cooled to room temperature. Strip samples were obtained by wire cutting, and the microstructure, conductivity, and mechanical properties were analyzed and tested.

[0099] Embodiment 7:

[0100] This embodiment is made on the basis of embodiment 2, and the main differences are: different magnesium content and different aging treatment issues.

[0101] Prepare raw materials according to the alloy component mass fraction of Ni 1.80%, Si 0.62%, Co 1.1%, Mg 0.24%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%. Add the prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles into the graphite crucible in the vacuum induction melting furnace, seal the high-purity magnesium particles into the secondary feeding copper tube, close the melting furnace and extract the air to 13Pa, and then introduce argon gas to the pressure of 0.04-0.05Mpa. Completely melt the metal particles in the crucible by induction heating, let it stand for 2-3 minutes, add the high-purity magnesium particles into the molten metal through the secondary feeding copper tube, let it stand for 3-5 minutes, and finally pour the alloy melt into the mold, cool it to room temperature and take out the ingot. The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was cooled to room temperature by water. After being polished with sandpaper, the surface impurities were cleaned with acetone and alcohol. The alloy sample was rough rolled on a two-roll mill. The rolling conditions were room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction was 90%. Then the sample was fine rolled on a four-roll mill. The rolling conditions were room temperature, single pass 10%, roll speed 20 rpm, and finishing rolling reduction was 90%. The total rolling reduction was 99%. The cold-rolled alloy sample was aged at 400℃ for 40min, and then air-cooled to room temperature. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.

[0102] Comparative Example 3:

[0103] Comparative Example 3 is made on the basis of Comparative Example 1. Raw materials are prepared according to the alloy component mass fractions of Ni of 1.80%, Si of 0.62%, Co of 1.1%, Mg of 0%, and the balance of copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%. The prepared high-purity copper particles, nickel particles, silicon particles and cobalt particles are added to the graphite crucible in the vacuum induction melting furnace, and the high-purity magnesium particles are sealed in the secondary feeding copper tube. The melting furnace is closed and the air is extracted to 13Pa, and then argon is introduced to the pressure of 0.04-0.05Mpa. The metal particles in the crucible are completely melted by induction heating, and the mixture is allowed to stand for 2-3 minutes. The high-purity magnesium particles are added to the molten metal through the secondary feeding copper tube, and the mixture is allowed to stand for 3-5 minutes. Finally, the alloy melt is poured into a mold, and the ingot is taken out after cooling to room temperature. The alloy ingot was cut into blocks by wire cutting, and then solution treated. After being kept at 850℃ for 5h, it was cooled to room temperature by water. After being polished with sandpaper, the surface impurities were cleaned with acetone and alcohol. The alloy sample was rough rolled on a two-roll mill. The rolling conditions were room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction was 90%. Then the sample was fine rolled on a four-roll mill. The rolling conditions were room temperature, single pass 10%, roll speed 20 rpm, and finishing rolling reduction was 90%. The total rolling reduction was 99%. The cold-rolled alloy sample was aged at 400℃ for 10min, and then air-cooled to room temperature. Strip samples were obtained by wire cutting, and the microstructure, conductivity and mechanical properties were analyzed and tested.

[0104] Example 6, Example 7 and Comparative Example 3 were set as the third sample group, and the test results obtained were as follows:

[0105] Table 9 Mechanical properties test results of the third group of samples

[0106]

[0107]

[0108] Table 10 Mechanical property increment of the third group of specimens

[0109] Time limit 0% Mg 0.12% Mg 0.24% Mg min MPa MPa MPa 0 0 28.32% 37.07% 10 0 57.31% 9.82% 20 0 66.62% 15.00% 30 0 42.60% -5.80% 40 0 35.46% 16.51% average value 46.06% 15.2%

[0110] Table 11 Test results of conductivity of the third group of samples

[0111] Time limit 0% Mg 0.12% Mg 0.24% Mg min %IACS %IACS %IACS 0 39.90782 38.15191 36.46133 10 51.65221 44.41443 45.12694 20 50.70104 46.16517 44.48724 30 51.30139 47.23898 47.85764 40 53.61382 48.39688 45.02679

[0112] Table 12 Conductivity increment of the third group of samples

[0113] Time limit 0% Mg 0.12% Mg 0.24% Mg min 0 0 -4.40% -8.64% 10 0 -14.01% -12.63% 20 0 -8.95% -12.26% 30 0 -7.92% -6.71% 40 0 -9.73% -16.02% average value -9% -11.25%

[0114] Combining the contents in Tables 9 to 12, it can be seen that in the third group of samples, when the content of magnesium element increases to 0.12%, its average mechanical properties increase by 46.06%, but its electrical conductivity only changes by 9%.

[0115] In the third group of samples, when the magnesium content increases to 0.24%, the average mechanical properties increase by 15.2%, but the electrical conductivity changes by only 11.25%.

[0116] Table 13 Changes in average mechanical properties and electrical conductivity of samples from the first to the third group

[0117] parameter 0.12% Mg 0.24% Mg Changes in mechanical properties of the first group of specimens +32.76% +30.2% Changes in mechanical properties of the second group of specimens +39.91% +39.65% Changes in mechanical properties of the third group of specimens +46.06% +15.2% Average value of mechanical properties change +39.58% 28.35% Changes in conductivity of the first group of samples -4% -9.66% Changes in conductivity of the second group of samples -8.4% -11.39% Changes in conductivity of the third group of samples -9% -11.25% Average value of conductivity change -7% -10.8%

[0118] A comprehensive comparison of the three groups of samples shows that when the magnesium content increases to 0.12%, the average change in mechanical properties is 39.58%, but the average change in electrical conductivity is only reduced by 7%. The average change in mechanical properties is 5.65 times that of electrical conductivity.

[0119] When the magnesium content increases to 0.24%, the average change in mechanical properties is 28.35%, but the average change in electrical conductivity is only reduced by 10.8%. The average change in mechanical properties is 2.6 times that of electrical conductivity. It can be seen that by introducing magnesium, the mechanical properties of the material itself can be effectively improved while the change in electrical conductivity is small.

[0120] Example 8

[0121] This embodiment provides a method for preparing a copper-nickel-silicon-cobalt-magnesium alloy, which is used for the nickel-silicon-cobalt-magnesium alloy provided in Example 1, comprising the following steps:

[0122] Putting high-purity copper raw materials, nickel raw materials, silicon raw materials and cobalt raw materials into a smelting device for melting;

[0123] Specifically, raw materials are prepared according to the alloy component mass fractions of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%.

[0124] The smelting equipment is vacuumed to reduce the gas pressure inside the smelting equipment to below 20Pa; inert gas is introduced into the smelting equipment to increase the gas pressure inside the smelting equipment to between 0.04-0.05Mpa;

[0125] A magnesium raw material is introduced into a smelting device, and the smelting device is started to melt the magnesium raw material;

[0126] The molten metal obtained after smelting is allowed to stand, and after cooling to room temperature, the alloy ingot is taken out;

[0127] The obtained alloy ingot is subjected to a solution treatment operation, wherein the solution treatment temperature is 800° C.-900° C. and the solution treatment time is 5 hours;

[0128] The alloy ingot after solution treatment is subjected to rolling operation, including:

[0129] The alloy sample was kept at 760℃-800℃ for 0.5h;

[0130] Hot rolling was carried out on a two-roll mill, with the rolling conditions of 30% per pass, 30 rpm of roll speed, and 50-55% reduction in hot rolling;

[0131] After the alloy sample was air-cooled to room temperature, it was rough-rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 80-85%.

[0132] The rolled alloy is aged at 300°C for 0.5h-4h and then air-cooled to room temperature.

[0133] Example 9

[0134] This embodiment provides a method for preparing a copper-nickel-silicon-cobalt-magnesium alloy, which is used for the nickel-silicon-cobalt-magnesium alloy provided in Example 1, comprising the following steps:

[0135] Putting high-purity copper raw materials, nickel raw materials, silicon raw materials and cobalt raw materials into a smelting device for melting;

[0136] Specifically, raw materials are prepared according to the alloy component mass fractions of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.24%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%.

[0137] The smelting equipment is vacuumed to reduce the gas pressure inside the smelting equipment to below 20Pa; inert gas is introduced into the smelting equipment to increase the gas pressure inside the smelting equipment to between 0.04-0.05Mpa;

[0138] A magnesium raw material is introduced into a smelting device, and the smelting device is started to melt the magnesium raw material;

[0139] The molten metal obtained after smelting is allowed to stand, and after cooling to room temperature, the alloy ingot is taken out;

[0140] The obtained alloy ingot is subjected to a solution treatment operation, wherein the solution treatment temperature is 800° C.-900° C. and the solution treatment time is 5 hours;

[0141] The alloy ingot after solution treatment is subjected to rolling operation, including:

[0142] The alloy sample was kept at 760℃-800℃ for 0.5h;

[0143] Hot rolling was carried out on a two-roll mill, with the rolling conditions of 30% per pass, 30 rpm of roll speed, and 50-55% reduction in hot rolling;

[0144] After the alloy sample was air-cooled to room temperature, it was rough-rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 80-85%.

[0145] The rolled alloy is aged at 300°C for 0.5h-4h and then air-cooled to room temperature.

[0146] Comparative Example 4

[0147] Comparative Example 4 is prepared on the basis of Example 8, and is different from Example 8 in that, in Comparative Example 4, the content of magnesium element is 0.

[0148] Example 8, Example 9 and Comparative Example 4 were used as the fourth group of samples, and the test results obtained were as follows: Table 14 Mechanical properties of the fourth group of samples

[0149] Can test results

[0150] Time limit 0% Mg 0.12% Mg 0.24% Mg h MPa MPa MPa 0 590.9 706.5 784.6 0.5 602.1 755.7 784.6 1 532.8 737.8 739.4 2 532.9 709.1 790.3 4 533.3 734.7 766.9

[0151] Table 15 Mechanical property increment of the fourth group of specimens

[0152] Time limit 0% Mg 0.12% Mg 0.24% Mg h 0 0 19.56% 32.78% 0.5 0 25.51% 30.31% 1 0 38.48% 38.78% 2 0 33.06% 48.30% 4 0 37.76% 43.80% average value 30.88% 38.79%

[0153] Table 16 Test results of the fourth group of conductivity of samples

[0154]

[0155]

[0156] Table 17 Conductivity increment of the fourth group of samples

[0157] Time limit 0% Mg 0.12% Mg 0.24% Mg h 0 0 -22.61% -18.23% 0.5 0 -9.32% -11.00% 1 0 -12.19% -15.98% 2 0 -6.64% -13.69% 4 0 -2.66% -12.64% average value -10.68% -14.31%

[0158] Combined with the contents recorded in Tables 14 to 17, when the magnesium element accounts for 0.12%, the average mechanical properties change by 30.88%, and the electrical conductivity changes by 10.68%.

[0159] When the magnesium element accounts for 0.24%, the average mechanical properties change by 38.79%, and the conductivity changes by 14.31%.

[0160] Example 10

[0161] This embodiment provides a method for preparing a copper-nickel-silicon-cobalt-magnesium alloy, which is used for the nickel-silicon-cobalt-magnesium alloy provided in Example 1, comprising the following steps:

[0162] Putting high-purity copper raw materials, nickel raw materials, silicon raw materials and cobalt raw materials into a smelting device for melting;

[0163] Specifically, raw materials are prepared according to the alloy component mass fractions of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%.

[0164] The smelting equipment is vacuumed to reduce the gas pressure inside the smelting equipment to below 20Pa; inert gas is introduced into the smelting equipment to increase the gas pressure inside the smelting equipment to between 0.04-0.05Mpa;

[0165] A magnesium raw material is introduced into a smelting device, and the smelting device is started to melt the magnesium raw material;

[0166] The molten metal obtained after smelting is allowed to stand, and after cooling to room temperature, the alloy ingot is taken out;

[0167] The obtained alloy ingot is subjected to a solution treatment operation, wherein the solution treatment temperature is 800° C.-900° C. and the solution treatment time is 5 hours;

[0168] The alloy ingot after solution treatment is subjected to rolling operation, including:

[0169] The alloy sample was kept at 760℃-800℃ for 0.5h;

[0170] Hot rolling was carried out on a two-roll mill, with the rolling conditions of 30% per pass, 30 rpm of roll speed, and 50-55% reduction in hot rolling;

[0171] After the alloy sample was air-cooled to room temperature, it was rough-rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 80-85%.

[0172] The rolled alloy is aged at 350°C for 0.5h-4h and then air-cooled to room temperature.

[0173] Embodiment 11

[0174] This embodiment provides a method for preparing a copper-nickel-silicon-cobalt-magnesium alloy, which is used for the nickel-silicon-cobalt-magnesium alloy provided in Example 1, comprising the following steps:

[0175] Putting high-purity copper raw materials, nickel raw materials, silicon raw materials and cobalt raw materials into a smelting device for melting;

[0176] Specifically, raw materials are prepared according to the alloy component mass fractions of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.24%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%.

[0177] The smelting equipment is vacuumed to reduce the gas pressure inside the smelting equipment to below 20Pa; inert gas is introduced into the smelting equipment to increase the gas pressure inside the smelting equipment to between 0.04-0.05Mpa;

[0178] A magnesium raw material is introduced into a smelting device, and the smelting device is started to melt the magnesium raw material;

[0179] The molten metal obtained after smelting is allowed to stand, and after cooling to room temperature, the alloy ingot is taken out;

[0180] The obtained alloy ingot is subjected to a solution treatment operation, wherein the solution treatment temperature is 800° C.-900° C. and the solution treatment time is 5 hours;

[0181] The alloy ingot after solution treatment is subjected to rolling operation, including:

[0182] The alloy sample was kept at 760℃-800℃ for 0.5h;

[0183] Hot rolling was carried out on a two-roll mill, with the rolling conditions of 30% per pass, 30 rpm of roll speed, and 50-55% reduction in hot rolling;

[0184] After the alloy sample was air-cooled to room temperature, it was rough-rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 80-85%.

[0185] The rolled alloy is aged at 350°C for 0.5h-4h and then air-cooled to room temperature.

[0186] Comparative Example 5

[0187] Comparative Example 5 is prepared on the basis of Example 10, and differs from Example 10 in that, in Example 10, the magnesium content is 0.

[0188] Example 10, Example 11 and Comparative Example 5 were set as the fifth sample group, and the test results obtained were as follows:

[0189] Table 18 Test results of mechanical properties of the fifth group of specimens

[0190] Time limit 0% Mg 0.12% Mg 0.24% Mg h MPa MPa MPa 0 590.9 706.5 784.6 0.5 515.9 711.1 704.1 1 402.5 676.1 726.5 2 466.5 629.6 635.7 4 434.9 629.6 684.4

[0191] Table 19 Mechanical property increment of the fifth group of specimens

[0192] Time limit 0% Mg 0.12% Mg 0.24% Mg h 0 0 19.56% 32.78% 0.5 0 37.84% 36.48% 1 0 67.98% 80.50% 2 0 34.96% 36.27% 4 0 44.77% 57.37% average value 41.02% 48.68%

[0193] Table 20 Test results of conductivity of the fifth group of samples

[0194]

[0195]

[0196] Table 21 Conductivity increment of the fifth group of samples

[0197] Time limit 0% Mg 0.12% Mg 0.24% Mg h 0 0 -22.61% -18.23% 0.5 0 -6.62% -15.24% 1 0 -3.23% -12.74% 2 0 4.69% -8.65% 4 0 -8.09% -13.09% average value -7.17% -13.59%

[0198] Combined with the contents recorded in Tables 18 to 21, when the magnesium element accounts for 0.12%, the average mechanical properties change by 41.02% and the electrical conductivity changes by 7.17%.

[0199] When the magnesium element accounts for 0.24%, the average mechanical properties change by 48.68%, and the conductivity changes by 13.59%.

[0200] Example 12

[0201] This embodiment provides a method for preparing a copper-nickel-silicon-cobalt-magnesium alloy, which is used for the nickel-silicon-cobalt-magnesium alloy provided in Example 1, comprising the following steps:

[0202] Putting high-purity copper raw materials, nickel raw materials, silicon raw materials and cobalt raw materials into a smelting device for melting;

[0203] Specifically, raw materials are prepared according to the alloy component mass fractions of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%.

[0204] The smelting equipment is vacuumed to reduce the gas pressure inside the smelting equipment to below 20Pa; inert gas is introduced into the smelting equipment to increase the gas pressure inside the smelting equipment to between 0.04-0.05Mpa;

[0205] A magnesium raw material is introduced into a smelting device, and the smelting device is started to melt the magnesium raw material;

[0206] The molten metal obtained after smelting is allowed to stand, and after cooling to room temperature, the alloy ingot is taken out;

[0207] The obtained alloy ingot is subjected to a solution treatment operation, wherein the solution treatment temperature is 800° C.-900° C. and the solution treatment time is 5 hours;

[0208] The alloy ingot after solution treatment is subjected to rolling operation, including:

[0209] The alloy sample was kept at 760℃-800℃ for 0.5h;

[0210] Hot rolling was carried out on a two-roll mill, with the rolling conditions of 30% per pass, 30 rpm of roll speed, and 50-55% reduction in hot rolling;

[0211] After the alloy sample was air-cooled to room temperature, it was rough-rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 80-85%.

[0212] The rolled alloy is aged at 400°C for 0.5h-4h and then air-cooled to room temperature.

[0213] Example 13

[0214] This embodiment provides a method for preparing a copper-nickel-silicon-cobalt-magnesium alloy, which is used for the nickel-silicon-cobalt-magnesium alloy provided in Example 1, comprising the following steps:

[0215] Putting high-purity copper raw materials, nickel raw materials, silicon raw materials and cobalt raw materials into a smelting device for melting;

[0216] Specifically, raw materials are prepared according to the alloy component mass fractions of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.24%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%.

[0217] The smelting equipment is vacuumed to reduce the gas pressure inside the smelting equipment to below 20Pa; inert gas is introduced into the smelting equipment to increase the gas pressure inside the smelting equipment to between 0.04-0.05Mpa;

[0218] A magnesium raw material is introduced into a smelting device, and the smelting device is started to melt the magnesium raw material;

[0219] The molten metal obtained after smelting is allowed to stand, and after cooling to room temperature, the alloy ingot is taken out;

[0220] The obtained alloy ingot is subjected to a solution treatment operation, wherein the solution treatment temperature is 800° C.-900° C. and the solution treatment time is 5 hours;

[0221] The alloy ingot after solution treatment is subjected to rolling operation, including:

[0222] The alloy sample was kept at 760℃-800℃ for 0.5h;

[0223] Hot rolling was carried out on a two-roll mill, with the rolling conditions of 30% per pass, 30 rpm of roll speed, and 50-55% reduction in hot rolling;

[0224] After the alloy sample was air-cooled to room temperature, it was rough-rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 80-85%.

[0225] The rolled alloy is aged at 400°C for 0.5h-4h and then air-cooled to room temperature.

[0226] Comparative Example 6

[0227] Comparative Example 6 is made on the basis of Example 12. Compared with Example 12, the content of magnesium element in Comparative Example 6 is 0.

[0228] Example 12, Example 13 and Comparative Example 6 were set as the sixth sample group, and the test results obtained were as follows:

[0229] Table 22 Mechanical properties test results of the sixth group of samples

[0230] Time limit 0% Mg 0.12% Mg 0.24% Mg h MPa MPa MPa 0 590.9 706.5 784.6 0.5 398.3 631.1 637.5 1 397.5 593.1 625.7 2 363.6 530 606.6 4 336.4 499.2 586.6

[0231] Table 23 Mechanical property increment of the sixth group of specimens

[0232] Time limit 0% Mg 0.12% Mg 0.24% Mg h 0 0 19.56% 32.78% 0.5 0 58.45% 60.06% 1 0 49.21% 57.41% 2 0 45.76% 66.83% 4 0 48.39% 74.38% average value 44.28% 58.29%

[0233] Table 24 Test results of conductivity of the sixth group of samples

[0234] Time limit 0% Mg 0.12% Mg 0.24% Mg h %IACS %IACS %IACS 0 47.4875 36.75054 38.82898 0.5 52.64728 47.19631 44.36604 1 50.52195 47.55141 45.1794 2 50.71382 48.4968 44.119 4 51.91675 49.74485 45.50325

[0235] Table 25 Conductivity increment of the sixth group of samples

[0236] Time limit 0% Mg 0.12% Mg 0.24% Mg h 0 0 -22.61% -18.23% 0.5 0 -10.35% -15.73% 1 0 -5.88% -10.57% 2 0 -4.37% -13.00% 4 0 -4.18% -12.35% average value -9.48% -13.98%

[0237] Combined with the contents recorded in Tables 21 to 25, when the magnesium element accounts for 0.12%, the average mechanical properties change by 44.28%, and the conductive properties change by 9.48%.

[0238] When the magnesium element accounts for 0.24%, the average mechanical properties change by 58.29%, and the conductivity changes by 13.98%.

[0239] Embodiment 14

[0240] This embodiment provides a method for preparing a copper-nickel-silicon-cobalt-magnesium alloy, which is used for the nickel-silicon-cobalt-magnesium alloy provided in Example 1, comprising the following steps:

[0241] Putting high-purity copper raw materials, nickel raw materials, silicon raw materials and cobalt raw materials into a smelting device for melting;

[0242] Specifically, raw materials are prepared according to the alloy component mass fractions of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.12%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%.

[0243] The smelting equipment is vacuumed to reduce the gas pressure inside the smelting equipment to below 20Pa; inert gas is introduced into the smelting equipment to increase the gas pressure inside the smelting equipment to between 0.04-0.05Mpa;

[0244] A magnesium raw material is introduced into a smelting device, and the smelting device is started to melt the magnesium raw material;

[0245] The molten metal obtained after smelting is allowed to stand, and after cooling to room temperature, the alloy ingot is taken out;

[0246] The obtained alloy ingot is subjected to a solution treatment operation, wherein the solution treatment temperature is 800° C.-900° C. and the solution treatment time is 5 hours;

[0247] The alloy ingot after solution treatment is subjected to rolling operation, including:

[0248] The alloy sample was kept at 760℃-800℃ for 0.5h;

[0249] Hot rolling was carried out on a two-roll mill, with the rolling conditions of 30% per pass, 30 rpm of roll speed, and 50-55% reduction in hot rolling;

[0250] After the alloy sample was air-cooled to room temperature, it was rough-rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 80-85%.

[0251] The rolled alloy is aged at 450°C for 0.5h-4h and then air-cooled to room temperature.

[0252] Embodiment 15

[0253] This embodiment provides a method for preparing a copper-nickel-silicon-cobalt-magnesium alloy, which is used for the nickel-silicon-cobalt-magnesium alloy provided in Example 1, comprising the following steps:

[0254] Putting high-purity copper raw materials, nickel raw materials, silicon raw materials and cobalt raw materials into a smelting device for melting;

[0255] Specifically, raw materials are prepared according to the alloy component mass fractions of Ni: 1.80%, Si: 0.62%, Co: 1.1%, Mg: 0.24%, and the balance is copper, wherein the purity of Cu is ≥99.99%, the purity of Ni is ≥99.99%, the purity of Si is ≥99.99%, and the purity of Co is ≥99.99%.

[0256] The smelting equipment is vacuumed to reduce the gas pressure inside the smelting equipment to below 20Pa; inert gas is introduced into the smelting equipment to increase the gas pressure inside the smelting equipment to between 0.04-0.05Mpa;

[0257] A magnesium raw material is introduced into a smelting device, and the smelting device is started to melt the magnesium raw material;

[0258] The molten metal obtained after smelting is allowed to stand, and after cooling to room temperature, the alloy ingot is taken out;

[0259] The obtained alloy ingot is subjected to a solution treatment operation, wherein the solution treatment temperature is 800° C.-900° C. and the solution treatment time is 5 hours;

[0260] The alloy ingot after solution treatment is subjected to rolling operation, including:

[0261] The alloy sample was kept at 760℃-800℃ for 0.5h;

[0262] Hot rolling was carried out on a two-roll mill, with the rolling conditions of 30% per pass, 30 rpm of roll speed, and 50-55% reduction in hot rolling;

[0263] After the alloy sample was air-cooled to room temperature, it was rough-rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 80-85%.

[0264] The rolled alloy is aged at 450°C for 0.5h-4h and then air-cooled to room temperature.

[0265] Comparative Example 7

[0266] Comparative Example 7 is made on the basis of Example 14. The difference from Example 14 is that the magnesium content in Comparative Document 7 is 0.

[0267] Example 14, Example 15 and Comparative Example 7 were set as the seventh sample group, and the test results obtained were as follows:

[0268] Table 26 Mechanical properties test results of the seventh group of samples

[0269] Time limit 0% Mg 0.12% Mg 0.24% Mg h MPa MPa MPa 0 590.9 706.5 784.6 0.5 368.7 552.9 513 1 368.5 514.2 522.4 2 319.6 435.6 493.5 4 303.8 445 426.8

[0270] Table 27 Mechanical properties increment of the seventh group of specimens

[0271] Time limit 0% Mg 0.12% Mg 0.24% Mg h 0 0 19.56% 32.78% 0.5 0 49.96% 39.14% 1 0 39.54% 41.76% 2 0 36.30% 54.41% 4 0 46.48% 40.49% average value 38.37% 41.72%

[0272] Table 28 Test results of conductivity of the seventh group of samples

[0273] Time limit 0% Mg 0.12% Mg 0.24% Mg h %IACS %IACS %IACS 0 47.4875 36.75054 38.82898 0.5 51.32472 47.40258 44.33213 1 51.84251 49.17054 45.17869 2 51.55078 51.05721 46.59814 4 50.71121 52.0571 46.84002

[0274] Table 29 Conductivity increment of sample group 7

[0275]

[0276]

[0277] Combined with the contents recorded in Tables 26 to 29, when the magnesium element accounts for 0.12%, the average mechanical properties change by 38.37%, and the electrical conductivity changes by 6.74%.

[0278] When the magnesium element accounts for 0.24%, the average mechanical properties change by 41.72%, and the conductivity changes by 12.39%.

[0279] Table 30 Changes in average mechanical properties and electrical conductivity of samples from group 4 to group 7

[0280] parameter 0.12% Mg 0.24% Mg Changes in mechanical properties of the fourth group of specimens 30.88% 38.79% Changes in mechanical properties of the fifth group of specimens 41.02% 48.68% Changes in mechanical properties of the sixth group of specimens 44.28% 58.29% Changes in mechanical properties of the seventh group of samples 38.37% 41.72% Average value of mechanical properties change 38.64% 46.87% Changes in conductivity of the fourth group of samples -10.68% -14.31% Changes in conductivity of the fifth group of samples -7.17% -13.59% Changes in conductivity of sample group 6 -9.48% -13.98% Changes in conductivity of sample group 7 -6.74% -12.39% Average value of conductivity change -8.52% -13.57%

[0281] A comprehensive comparison of the fourth to seventh groups of samples shows that when the magnesium content increases to 0.12%, the average change in the average mechanical properties is 38.64%, but the average change in the conductivity is only reduced by 8.52%. The change in the average mechanical properties is 4.53 times that of the conductivity.

[0282] When the magnesium content increases to 0.24%, the average change in mechanical properties is 46.87%, but the average change in electrical conductivity is only reduced by 13.57%. The change in mechanical properties is 3.45 times that of electrical conductivity.

[0283] In the above embodiment, the samples obtained by processing need to be tested for conductivity and mechanical properties respectively. The specific test methods are as follows:

[0284] 1. The test method for conductivity is as follows:

[0285] The resistance of the strip was measured using a sample with a size of 100mmX10mmX0.2mm (±0.01) using a ZY9987 digital microohmmeter, and the resistivity was calculated using the formula:

[0286] ρ=RS / L (1-1)

[0287] Where ρ is resistivity (μm.cm); R is resistance (μm); S is cross-sectional area (cm2); L is effective distance (cm). The conductivity σ(Sm-1) of the composite material is calculated by formula (1-1):

[0288] σ=1 / ρ (1-2)

[0289] Internationally, annealed copper wire with a density of 8.89 g / cm3, a length of 1 m, a mass of 1 g, and a resistance of 0.15328 Ω is used as the measurement standard. At 20°C, the conductivity of the annealed copper wire is 58.0 MS / m, which is determined to be 100% IACS (International Annealed Copper Standard). Finally, the conductivity (% IACS) of the composite material is calculated according to the formula shown in (1-3). The units must be unified when calculating.

[0290] Conductivity (%IACS) = Conductivity (MS / m) / 58.0 * 100% (1-3)

[0291] 2. The test methods for mechanics are as follows:

[0292] Mechanical property testing involves material strength testing. The material strength test is measured using a Meters CMT5205 electronic universal testing machine with a set tensile rate of 2 mm / min. A 0.2 mm (± 0.01) thick strip is processed by wire cutting. Fig.17 As shown, the tensile direction is consistent with the rolling direction, and the sample is polished with 800# sandpaper before testing. To ensure the accuracy of the test results, at least 3 tensile samples are required for each test sample in different states.

[0293] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A nickel-silicon-cobalt-magnesium alloy, characterized in that: Calculated by mass fraction of the alloy components, Ni is 1.80%, Si is 0.62%, Co is 1.1%, Mg is 0.12%-0.24%, and the balance is copper.

2. A method for preparing a copper-nickel-silicon-cobalt-magnesium alloy, for preparing the nickel-silicon-cobalt-magnesium alloy according to claim 1, characterized in that: The steps include: Putting high-purity copper raw materials, nickel raw materials, silicon raw materials and cobalt raw materials into a smelting device for melting; Evacuate the smelting equipment to reduce the pressure inside the smelting equipment to below 20Pa; Introduce inert gas into the smelting equipment to increase the pressure inside the smelting equipment to between 0.04-0.05Mpa; A magnesium raw material is introduced into a smelting device, and the smelting device is started to melt the magnesium raw material; The molten metal obtained after smelting is allowed to stand, and after cooling to room temperature, the alloy ingot is taken out; The obtained alloy ingot is subjected to a solution treatment operation, wherein the solution treatment temperature is 800° C.-900° C. and the solution treatment time is 5 hours; The alloy ingot after solution treatment is subjected to rolling operation, including: Rough rolling step: rolling temperature is room temperature, single pass is 20%, roll speed is 30 rpm, and rough rolling reduction is 90%; Finishing rolling steps: rolling temperature is room temperature, single pass is 10%, roll speed is 20 rpm, finishing rolling reduction is 90%; total rolling reduction is 99%; After the rolling operation step, the method further includes: performing aging treatment on the rolled alloy at 300-400° C. for 10-40 minutes, and air cooling to room temperature after aging.

3. The method for preparing a copper-nickel-silicon-cobalt-magnesium alloy according to claim 2, characterized in that: The vacuum induction melting furnace is provided with a copper tube, and the magnesium raw material is introduced into the vacuum induction melting furnace through the copper tube.

4. The method for preparing a copper-nickel-silicon-cobalt-magnesium alloy according to claim 3, characterized in that: Before the rolling operation step, the alloy ingot is cleaned, including: grinding with sandpaper and cleaning with acetone and alcohol.

5. A method for preparing a copper-nickel-silicon-cobalt-magnesium alloy, for preparing the nickel-silicon-cobalt-magnesium alloy according to claim 1, characterized in that: The steps include: Putting high-purity copper raw materials, nickel raw materials, silicon raw materials and cobalt raw materials into a smelting device for melting; Evacuate the smelting equipment to reduce the pressure inside the smelting equipment to below 20Pa; Introduce inert gas into the smelting equipment to increase the pressure inside the smelting equipment to between 0.04-0.05Mpa; A magnesium raw material is introduced into a smelting device, and the smelting device is started to melt the magnesium raw material; The molten metal obtained after smelting is allowed to stand, and after cooling to room temperature, the alloy ingot is taken out; The obtained alloy ingot is subjected to a solution treatment operation, wherein the solution treatment temperature is 800° C.-900° C. and the solution treatment time is 5 hours; The alloy ingot after solution treatment is subjected to rolling operation, including: The alloy sample was kept at 760℃-800℃ for 0.5h; Hot rolling was carried out on a two-roll mill, with the rolling conditions of 30% per pass, 30 rpm of roll speed, and 50-55% reduction in hot rolling; After the alloy sample was air-cooled to room temperature, it was rough-rolled on a two-roll mill. The rolling conditions were: room temperature, single pass 20%, roll speed 30 rpm, and rough rolling reduction of 80-85%. The rolled alloy is aged at 430°C for 0.5h-4h and then air-cooled to room temperature.

6. The method for preparing a copper-nickel-silicon-cobalt-magnesium alloy according to claim 5, characterized in that: The vacuum induction melting furnace is provided with a copper tube, and the magnesium raw material is introduced into the vacuum induction melting furnace through the copper tube.

7. The method for preparing the copper-nickel-silicon-cobalt-magnesium alloy according to claim 5, characterized in that: Before the rolling operation step, the alloy ingot is cleaned, including: grinding with sandpaper and cleaning with acetone and alcohol.

Citation Information

Patent Citations

  • High-strength and high-elasticity copper-nickel-silicon-cobalt-system lead frame machining technology

    CN107988512A

  • Preparation method of high-performance Cu-Ni-Si alloy based on microstructure design

    CN116179977A

  • Preparation method of copper alloy for lead frame with multi-scale precipitated phases

    CN118756078A

  • Copper alloy containing cobalt, nickel and silicon

    CN1671877A

  • Copper alloy containing cobalt, nickel and silicon

    JP2014095150A